Semilunar Sign of Trans-Mediastinal Herniation of Giant Bullae with Tension Hydropneumothrax - Tjan, Anastasia; Ayusta, I Made Dwija Putra; Mahiswara, Dewa Gde (Folia Medica Indonesiana, 2020)
Herniation of bulla across mediastinum is rare, while transmediastinal giant bulla herniation accompanied with hydropneumothorax is even rarer. We report a case of an 18 years old male with dyspnea came to emergency department with trans-mediastinal giant bulla herniation, which appears as semilunar sign on chest x-ray, and righthydropneumothoraks. It appeared that the giant bulla also infected by the presence of air fluid level within. Semilunar sign was seen on the contralateral left mediastinum as the hallmark finding for trans-mediastinal herniation of bulla. Chest CT further confirms the diagnosis. Subsequently chest tube insertion and symptomatic relives were given, however the patient end up dead after 2 days of observation. Heart and lung compression by the lesions were the cause of this patient poor outcome. Bullous lung disease should be evaluated thoroughly and not underestimated since it could cause severe disease progression.